Anti‐windup compensator design for power system subjected to time‐delay and actuator saturation. Issue 1 (23rd January 2019) - Obaiah, Maddela Chinna; Subudhi, Bidyadhar
Abstract : In this study, a delay‐dependent anti‐windup compensator (AWC) is designed for supplementary damping control (SDC) of flexible AC transmission system (FACTS) device to enhance the damping of inter‐area oscillations of the power system subjected to time‐delay and actuator saturation. By employing global signal measurements, an SDC of FACTS device is designed without considering the effect of time‐delay and actuator saturation to stabilise the power system using a robust output feedback controller with pole placement approach. Then, based on the generalised sector condition and Lyapunov–Krasovskii functional, an add‐on delay‐dependent AWC is designed to mitigate the adverse effect of time‐delay and actuator saturation non‐linearity. For the design of delay‐dependent AWC, sufficient conditions guarantee the asymptotic stability of the closed‐loop power system are formulated in the form of linear matrix inequalities (LMIs). These conditions are cast into the LMI‐based convex optimisation problem to compute the AWC gains. To evaluate the effectiveness of the proposed controller, non‐linear simulations were performed first using MATLAB/Simulink. Then, the authors implemented the proposed controller in real‐time using the Opal‐RT digital simulator. From the obtained results, it is observed that the proposed controller enhances the damping of inter‐area oscillations by compensating the effect of time delay and actuator saturation.